Causal effects of endometriosis stages and locations on menstruation, ovulation, reproductive function, and delivery modes: a two-sample Mendelian randomization study - Shen, Lin; Li, Jie; Zhang, Hanwang; Zhao, Yiqing (Frontiers in Endocrinology, 2024)
Background Endometriosis is a chronic inflammatory disease of women during their reproductive years. The relationship between the severity and location of endometriosis and menstruation, ovulation, reproductive function and mode of delivery remains unclear. Methods We explored the association between the various phenotypes of endometriosis and menstruation, ovulation, reproductive function, and mode of delivery, using two-sample Mendelian randomization (MR) and summary data on endometriosis stages and locations from the FinnGen consortium and women's menstruation, ovulation, reproductive function, and mode of delivery from OpenGWAS and ReproGen. Inverse-variance weighting was used for the primary MR analysis. In addition, a series of sensitivity analyses, confounding analyses, co-localization analyses and multivariate MR analyses were performed. Results MR analysis showed a negative effect of moderate to severe endometriosis on age at last live birth (OR=0.973, 95% CI: 0.960-0.986) and normal delivery (OR=0.999, 95%CI: 0.998-1.000, values for endpoint were excluded), ovarian endometriosis on age at last live birth (OR=0.976, 95% CI: 0.965-0.988) and normal delivery (OR=0.999, 95% CI: 0.998-1.000, values for endpoint were excluded), and fallopian tubal endometriosis on excessive irregular menstruation (OR=0.966, 95% CI: 0.942-0.990). Bidirectional MR analysis showed that age at menarche had a negative causal effect on intestinal endometriosis (OR=0.417, 95%CI: 0.216-0.804). All MR analyses were confirmed by sensitivity analyses, and only the genetic effects of moderate to severe endometriosis on normal delivery and age at last live birth were supported by co-localization evidence. Conclusion Our findings deepen the understanding of the relationship between various types of endometriosis and menstruation, ovulation, reproductive function and mode of delivery, and clarify the important role of moderate to severe endometriosis.